2015
DOI: 10.1186/s12964-015-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide – production, fate and role in redox signaling of tumor cells

Abstract: Hydrogen peroxide (H2O2) is involved in various signal transduction pathways and cell fate decisions. The mechanism of the so called “redox signaling” includes the H2O2-mediated reversible oxidation of redox sensitive cysteine residues in enzymes and transcription factors thereby altering their activities. Depending on its intracellular concentration and localization, H2O2 exhibits either pro- or anti-apoptotic activities. In comparison to normal cells, cancer cells are characterized by an increased H2O2 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
317
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 445 publications
(367 citation statements)
references
References 244 publications
7
317
2
2
Order By: Relevance
“…ROS or electrophilic agents modify redox-sensitive cysteine residues of Keap1, leading to conformational changes and the release of Nrf2, which in turn could translocate into the nucleus and initiate the transcriptional induction of its target proteins. 42 In our study, a strong upregulation of Nrf2 targets was observed, such as NQO1. Next to its role in the anti-oxidative defense, NQO1 is described to stabilize p53 and thus prevents its proteasomal degradation.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…ROS or electrophilic agents modify redox-sensitive cysteine residues of Keap1, leading to conformational changes and the release of Nrf2, which in turn could translocate into the nucleus and initiate the transcriptional induction of its target proteins. 42 In our study, a strong upregulation of Nrf2 targets was observed, such as NQO1. Next to its role in the anti-oxidative defense, NQO1 is described to stabilize p53 and thus prevents its proteasomal degradation.…”
Section: Discussionsupporting
confidence: 59%
“…The expression pattern of three of the upregulated proteins are controlled by the transcription factor Nrf2. 42 These include glucose 6-phosphate dehydrogenase (G6PD), peroxiredoxin 1 (PRXD1) and S-formylglutathione hydrolase (ESTD), all involved in mounting/maintaining the anti-oxidative defense. In addition, two ER-resident enzymes named protein disulfide isomerase (PDI) and calreticulin (CALR) were upregulated in response to MSA treatment.…”
Section: Msa-mediated Changes In the Protein Expression Pattern Of B1mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the superoxide anion and hydroxyl radical, the less reactive H 2 O 2 is involved in various signal transduction pathways in normal as well as in cancer cells, including proliferation and differentiation [189,190,reviewed in 191] as well as inflammation, phagocytosis and apoptosis [192]. The mechanism of "redox signaling" involves the H 2 O 2 -mediated reversible oxidation of specific amino acids in enzymes and transcription factors, thereby altering their activities [187,193].…”
Section: Hydrogen Peroxide As Signaling Moleculesmentioning
confidence: 99%
“…Increased ROS levels may play a significant role in cancer development by activating various signaling pathways [193,198]. Simply put, increased H 2 O 2 values may be perceived as "redox signaling".…”
Section: Hydrogen Peroxide As Signaling Moleculesmentioning
confidence: 99%